Infecção de sítio cirúrgico em cirurgias limpas de fraturas de fêmur em um hospital de grande porte de Belo Horizonte: incidência e fatores de risco - Hoberdan Oliveira Pereira (2012)
Infections resulting from surgical clean is important for its morbidity, mortality, and as a marker of quality of care. The interest in identifying risk factors for infections in surgical patients has increased among health professionals. Studies accordingly become increasingly necessary, since the surgical infections increase the length of hospitalization, cost of care and suffering of the patient. Surgery for correction of femoral fractures are frequent among surgical procedures. The objective of this work was to study the epidemiology of surgical site infection in patients undergoing clean surgery to correct fractures fêmur. Estudo historical cohort, identified the risk factors for surgical site infection (SSI) in patients undergoing surgery clean to fix fractures of the femur in a large hospital in Belo Horizonte. Data collection was made in the records of electronic medical records from July 2007 to July 2009. We collected data on patient characteristics, surgical procedures and surgical infections. Risk factors for infection were identified through statistical hypothesis testing bilateral level of significance of 5%. Continuous variables were evaluated by Student's t test. Categorical variables were analyzed using chi-square or Fisher's exact test when necessary. For each factor under study, we obtained a point estimate and confidence intervals of 95% for the relative risk. In the last stage of this work, we performed a multivariate analysis (logistic regression). The study included 432 patients who underwent correction clean fracture of the femur. The incidence rate of SSI was 4.9%and the risk factors identified were the presence of stroke (odds ratio - OR = 5.0) and hospitalization until surgery over four days (OR = 3,3). We compared the risk of SSI by a surgeon. The prolongation of hospitalization of patients and increased risk of death were complications of ISC found. For this action will be required involving the multidisciplinary team in assessing the clinical conditions of patients, reduced lengthof hospitalization and surgery and prevention of complications arising from infections.